On the presence of Thaumastocoridae (Hemiptera: Heteroptera) in Easter Island - Faundez, Eduardo; Salinas-Torres, Jaime; Carvajal, Mariom A. (My University, 2025)
The presence of true bug family Thaumastocoridae is recorded and discussed for the first time from the Oceanic Easter Island, Chile; with the species Thaumastocoris peregrinus Carpintero & Dellapé, 2006. Specimens were collected on Eucalyptus sp. Comments on the status of the invasion are provided.
Sobre la presencia de Thaumastocoridae (Hemiptera: Heteroptera) en Rapa Nui
Keywords: cimicomorpha; faunistics; hemiptera; new record